Alat Pencuci Tangan Movable Jenis Touchless Sebagai Alat Pemutus Rantai Penularan Covid-19 - Nasruddin Abdullah; Zainal Arif; Suheri Suheri (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2021)
One of the World Health Organization (WHO) protocols in breaking the chain of transmission of COVID-19 by washing hands. The availability of hand washing equipment with good standards and in accordance with WHO standards is urgently needed during a pandemic. The most effective way to wash your hands is by using soap and running water. In public places it is very difficult to get soap and running water, if any, using manual taps can increase transmission of COVID-19 because touching someone's hand on a faucet or a soap button will leave the virus and can spread the virus to future users. Use of the Touchless Type of Handwashing Tool can help reduce the spread of the hand washing process, because there is no touch at all on the components of the hand washing, using the Touchless Type of Handwashing Tool is expected to help people wash their hands with high standards. anywhere and anytime, so that in the end it can reduce the spread of the COVID-19 Virus in public areas. And it is hoped that this habit can also be continued not only during the pandemic period but in the continuing period after the pandemic ends. The installation of the tools will be carried out in a place where the aged people gather and can be moved easily.